SOCIO – ECONOMIC STATUS OF THE SCHEDULED TRIBES IN TELANGANA (With Special reference to BhadradriKothagudem District) - Parelli Sreenivas (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
Tribes are one of the many divergent groups that make up the Indian population. They continue to be disadvantaged primarily because they have been considered the smallest segment of Indian society since olden history. Cultural and geographic exclusion, a lack of appropriate healthcare facilities, an inability to meet basic needs, a loss of control over resources and assets, a lack of skills and education, poor nutrition, a lack of affordable housing, poor clean water and sanitation, insecurity to shocks, violence and crime, a denial of available to proper infrastructure facilities and technologies, and a lack of political freedom and voice are all factors that continue to disadvantage tribes. All of these obstacles can make life difficult for them. In light of these issues, the government is attempting to assist the tribes through various welfare schemes. The purpose of the study was to learn about the socioeconomic status of tribal people in the Bhadradri kothagudem district. To learn about their socio-cultural status, primary data were collected through a series of structured questionnaires. Discussions were held with tribal elders who were wise and insightful, and secondary data was gathered by reading tribal magazine articles and background. According to the findings of this study, the tribal’s socioeconomic situation has improved day by day. Though there are some issues in the area, such as poor communication, joblessness, power generation, social security, and clean drinking water, the primary education and health commonly known as “to be adequate, and the socio-cultural bonding between tribes is also very powerful.